2020
DOI: 10.1021/acs.inorgchem.0c01597
|View full text |Cite
|
Sign up to set email alerts
|

Langbeinite Phosphates KPbM2(PO4)3(M = Cr, Fe): Synthesis, Structure, Thermal Expansion, and Magnetic Properties Investigation

Abstract: New langbeinite-type phosphates KPbCr 2 (PO 4 ) 3 and KPbFe 2 (PO 4 ) 3 are synthesized by solution method and characterized by powder X-ray diffraction, infrared spectra, thermogravimetric and differential thermal analysis, scanning electron microscope, and energy dispersive X-ray analysis. Rietveld refinement reveals that both of the compounds crystallize in the cubic system with P2 1 3 space group, and the calculated lattice parameters for Cr and Fe phases are 9.7332(2) and 9.8325(7) Å, respectively. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 60 publications
(94 reference statements)
2
4
0
Order By: Relevance
“…198) and the experimental lattice constants are 9.7332 and 9.8325 Å for KPbCr 2 (PO 4 ) 3 and KPbFe 2 (PO 4 ) 3 , respectively. 21) Our optimized lattice constants are in good agreement with the experimental ones, which are 9.7945 and 9.8407 Å for KPbCr 2 (PO 4 ) 3 and KPbFe 2 (PO 4 ) 3 respectively.…”
Section: Calculation Methods and Detailssupporting
confidence: 82%
See 2 more Smart Citations
“…198) and the experimental lattice constants are 9.7332 and 9.8325 Å for KPbCr 2 (PO 4 ) 3 and KPbFe 2 (PO 4 ) 3 , respectively. 21) Our optimized lattice constants are in good agreement with the experimental ones, which are 9.7945 and 9.8407 Å for KPbCr 2 (PO 4 ) 3 and KPbFe 2 (PO 4 ) 3 respectively.…”
Section: Calculation Methods and Detailssupporting
confidence: 82%
“…These results are consistent with the experimental effective spin moments. 21) It is also found that different magnetic configurations have almost the same spin moments, which means that the magnetism in both phosphates is quite localized. Therefore, the differences in the total energies between different magnetic configurations are mainly contributed by the interatomic exchange interaction.…”
Section: Magnetic Property and Spin-exchange Interactionmentioning
confidence: 91%
See 1 more Smart Citation
“…19,20 Although, in general, the phosphorus atoms are only fourfold coordinated with oxygen atoms to form the PO 4 tetrahedra, the PO 4 tetrahedra can be further interconnected by sharing oxygen atoms to create a diversity of structure units, such as isolated [P n O 3n+1 ] (n+2)− (n ≥ 1) groups, [PO 3 ] ∞ chains, and [P n O 3n ] n− (n ≥ 3) rings. [21][22][23][24] Their rich structural diversity has resulted in the discovery of thousands of inorganic phosphates. [25][26][27] For example recently it has been noticed that mixed oxo-anionic phosphates with different degrees of phosphate group polymerization can also be synthesized, such as Na 4 Mg 3 ij(PO 4 ) 2 IJP 2 O 7 )], Rb 6 Bi 4 ij(PO 4 ) 2 IJP 2 -O 7 ) 3 ], Na 4 Ni 5 ij(PO 4 ) 2 IJP 2 O 7 ) 2 ], Na 7 Y 2 ij(P 2 O 7 ) 2 IJP 3 O 10 )], KMg 6 ij(P 2 -O 7 ) 2 IJP 3 O 10 )], Pb 2 Cd 3 ij(PO 4 ) 2 IJP 2 O 7 )], and TI 3 Ti 3 Oij(PO 4 ) 3 IJP 2 -O 7 )], [28][29][30][31][32][33][34] which even violate Pauling's fifth rule.…”
Section: Introductionmentioning
confidence: 99%
“…† The P-O stretching vibrations fall in the regions of 1086-921, 1074-937 and 1080-964 cm −1 , while the bending vibrations fall essentially in the region of 600-400 cm −1 . 51,52 The UV-vis-NIR diffuse reflectance spectra of compounds 1, 3 and 4 revealed that they exhibited wide transparency ranges from 500 to 2000 nm (Fig. S4 †).…”
Section: Ir and Uv-vis-nir Diffuse Reflectance Spectramentioning
confidence: 99%